Юридичні підвалини іноземної підприємницької ініціативи у кам’яновугільній та металургійній промисловості Південно-Східної України другої половини XIX ст. - Саманцов, О. П. (НТУ "ХПІ", 2014)
У статті автор досліджує вплив нормативно-правових актів на розвиток приватної підприємницької ініціативи у кам’яновугільній та металургійній промисловості Південно-Східної України. Звертається увага на те, що видання низькі нормативно-правових актів та підтримка приватної іноземної ініціативи Російським урядом сприяли переміщенню капіталів із економічно розвинених країн у визначені галузі.

In the article the author analyzes the influence of the normative and legislative acts on the development of the private entrepreneurial initiative in the coal-mining and metallurgical industry of South-Eastern Ukraine. The author draws the readers’ attention to the fact that the introduction into the circulation of the normative and legislative acts and the support of the private foreign initiative by the Russian government favored the shift of the capitals from the countries with the highly developed economy. Besides, there is accentuated the attention on the fact that the widely spread forms of the foreigners’ participation in the industrial manufacturing beginning with the 80s of the 19th century became the creation of the joint-stock companies. The author comes to the following conclusions that the southern regions of the Russian Empire were in the zone of the most favourable conditions and the governmental support that presented the additional opportunities to the foreign entrepreneurial activities. The above mentioned in its turn influenced in such a way that the private initiative goes beyond the industrial activities, expanding at the expense of the socially oriented actions.
Keywords: Південно-Східна Україна; історія України; кам’яновугільна промисловість; металургійна промисловість; private entrepreneurial initiative; South-Eastern Ukraine; metallurgical industry; coal-mining industry